GAMBARAN KARAKTERISTIK ASUPAN NUTRISI TERHADAP KEJADIAN STUNTING DI DESA SECANGGANG KABUPATEN LANGKAT - HANY SARAH PILIANG; ROBITAH ASFUR (LP2MTBM MAKARIOZ, 2021)
Stunting is a condition of failure to thrive in children under the age of five years old due to chronic malnutrition, whichtherefore then results in the child being too short for their age. Stunting is measured by height or height more than minus twostandard deviations from the median child growth according to WHO. Langkat, North Sumatra is the area that has the mostcases of stunting. This study aims to look at the characteristics of nutritional intake of children with stunting in the Village ofSecanggang, Langkat Regency. This study uses analytic descriptive with a cross sectional research design that meets theinclusion and exclusion criteria by purposive sampling. The number of samples in this study were 27 stunting toddlers basedon the data provided by the Public Health Centre and the 2013 Basic Health Research. With the use of a validatedquestionnaire that were then given to the parents of children with stunting. Stunting children were given high proportions ofnutritional intake, including those who receive MPASI after 6 months 26 people (96,3%), born within the ideal month 25people (92,6%), consuming fruits 24 people (88,9%) and mothers taking vitamins during pregnancy 23 people (85,2%).Nutritional intake factors that is associated with the incidence of stunting are birth weight <2500.